2019
DOI: 10.1055/s-0039-1694299
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Gastric Polyps

Abstract: Gastric lesions presenting as polyps becomes common these days. Many different underlying causes have been suspected with the origin of gastric polyps. Generally, a gastric polyp is considered as benign in the first impression unless proven otherwise. Though, they show a vast variety of malignant potentials. This literature is intended to describe and evaluate the variations, presentations, features, and potentials of gastric polypoid lesions. AbstractKeywords ► gastric polyp ► fundic gland polyps (FGP) ► hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Annually endoscopic examination is recommended for the follow-up. 21 They are common in females and at advanced age. In a retrospective study, the frequency of neuroendocrine tumor in patients with gastric polyps was found to be 3.5%, the mean age was 49.9 years, and the female/male ratio was 2.3/1.…”
Section: Discussionmentioning
confidence: 99%
“…Annually endoscopic examination is recommended for the follow-up. 21 They are common in females and at advanced age. In a retrospective study, the frequency of neuroendocrine tumor in patients with gastric polyps was found to be 3.5%, the mean age was 49.9 years, and the female/male ratio was 2.3/1.…”
Section: Discussionmentioning
confidence: 99%